Resúmenes XIII Congreso Latinoamericano de Microbiología e Higiene de Alimentos (COLMIC) - Jaime Andrés (Vitae, 2016)
Resúmenes XIII Congreso Latinoamericano de Microbiología e Higiene de Alimentos (COLMIC)